Kompetensi Guru dalam Penggunaan E-Learning pada Pembelajaran Al-Qur’an Hadits Kelas X di MAN 1 Bengkulu Utara - Ridho, Fuad; Riswanto, Riswanto; Mindani, Mindani (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2021)
The aim of carrying out this research is to determine the competency of 1st year class of Al-Qur'an Hadith teachers at MAN 1 North Bengkulu. To find out how to utilize and use e-learning by teachers in Al-Qur'an Hadith lessons in class the researcher in the thesis is qualitative. The data collection techniques used were observation, interviews and documentation. And the author's data analysis technique uses qualitative descriptive analysis. The results of the research show that the MAN 1 North Bengkulu school has used e-learning in teaching Al-Qur'an Hadith in 1st year class. The results of the research show that the use of e-learning at MAN 1 North Bengkulu has been running. Teachers have sufficient competence in using e-learning and the output is that students are increasingly enthusiastic in learning activities.